Pulmonary Regurgitation- Is the Future Percutaneous or Surgical? - Morgan, Gareth J. (Frontiers in Pediatrics, 2018)
For decades, surgical replacement of the pulmonary valve has been seen as the gold-standard technique. Until the advent of Medtronic’s Melody valve, it was the only option. Whilst radical changes in surgical techniques have not been forthcoming, rapid and substantial developments in the techniques and available technology for percutaneous valves now cause us to ask if the gold-standard moniker now belongs in the cath lab. This manuscript explores the recent history and future of a revolution in this large area of congenital cardiac practice.